Biot Theory Yields a Specific Storage Coefficient With Natural Deformation of Rock - Guangquan Li; Simeng Yang; Li Wang (Geofluids)
The traditional specific storage coefficient (Ss) was defined under two assumptions. One is that aquifer rock deforms only in the vertical direction, and the other is that the average rock stress remains unchanged. Consequently, Ss is irrelevant to the shear modulus of rock (G). In this paper, the Biot theory is used to derive a new specific storage coefficient (Ss∗) with the natural deformation of rock. Ss∗ appears to be relevant to G. Compressed glass beads and Berea sandstone are used for illustration. At frequencies lower than 10 kHz, the equation of groundwater flow with Ss∗ yields the same phase velocity and quality factor as the Biot theory, and therefore, it is capable of accurately predicting fluid pressure diffusion in the low-frequency regime. The results also show that Ss is 16%–17% higher than Ss∗. In conclusion, the latter one is superior to the former in its consistency with the Biot theory and unconstraint by the aforementioned two assumptions.